RELASI MAKNA DALAM BAHASA DAYAK BIDAYUH DIALEK BETEK - Clara, Moni; Madeten, Sisilya Saman; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This research is focused on observing the relation of meaning in Dayak Bidayuh Betek dialect. Bidayuh Dayak is a regional language in Siding Village, Siding District and has a different dialect with Dayak Bidayuh language. The relation of meaning meant in this research was that the researcher focused this research with the formulation of problems in the form of antonyms, synonyms and homonyms, regarding the relation of antonym meaning, synonyms, and homonyms. This research also aimed to describe the forms of antonyms, synonyms and homonyms, regarding the relation of the meanings of antonyms, synonyms, and homonyms in the Dayak Bidayuh Betek dialect. Based on research that has been done, researcher got 161 words. For the whole data is divided into Antonyms in total there were 70 words divided from absolute antonyms there were 22 words, gradations antonyms there were 24 words, relations antonyms there were 19 words and hierarchy there were 5 words. In total there were 61 synonyms of meaning relation in DayakBidayuhBetek dialect. Homonyms as a whole there were 30 words which are divided from homonyms there were 24 words, homographshad 3 words and homophones had 3 words.Keywords: The Relationship of Meanings in Bidayuh Dayak Betek Dialect